Lonimacranaldes A–C, three iridoids with novel skeletons from Lonicera macranthoides. Issue 38 (16th July 2019) - Mei, Yu-Dan; Li, Hai-Bo; Pang, Qian-Qian; Li, Ting; Pan, Da-Bo; Dai, Yi; Qin, Da-Peng; Meng, He; Yao, Xin-Sheng; Yu, Yang
Abstract : Lonimacranaldes A and B (1 and2 ), along with one biogenetically related intermediate, lonimacranalde C (3 ), were isolated from the flower buds of Lonicera macranthoides . Abstract : Lonimacranaldes A and B (1 and2 ), along with one biogenetically related intermediate, lonimacranalde C (3 ), were isolated from the flower buds of Lonicera macranthoides . Characterized by an iridoid structure and an additional C-6 unit with an aldehyde group, compounds1 and2 are the first examples of hybrid iridoids possessing an unexpected 6/5/6 fused tricyclic ring system, while compound3 serves as an important precursor for their generation. The structures of lonimacranaldes A–C (1–3 ) were revealed by extensive spectroscopic and X-ray diffraction analyses. A plausible biogenetic pathway for them was proposed. Compound3 showed anti-inflammatory activities by inhibiting the production of IL-6 on LPS-induced RAW 264.7 cells with an IC50 value of 6.33 μM.